Cybersecurity, attack and defense strategies : infrastructure security with Red Team and Blue Team tactics - Diogenes, Yuri; Ozkaya, Erdal (Packt Publishing, 2018)
With Cybercrime on a rise, Cybersecurity has become extremely vital to a large group of industries. Due to which, companies have started adopting the hard ways of preventing system breaches. This book will explore some Red Team and Blue Team tactics, where the Red Team tactics can be used in penetration for accessing sensitive data, and the ...